A STUDY OF A ROLE OF CHOLINERGIC COMPONENT IN ANTIDEPRESSIVE ACTION OF 2-OXOINDOLIN DERIVATIVE - Луценко, Р.В.; Сидоренко, А.Г.; Т. О. Дев’яткіна; Колісник, С.В. (World of Medicine and Biology, 2014)
It was studied an influence of E -38 substance in 12 mg/kg in comparison with imipramin (25 mg/kg) on effects of arekolin (15 mg/kg) and nikotin (10 mg/kg) at intraperitoneal injection per 1 hour to an usage of cholinotropic analizators during experiments on 60 state white rats Wistar. It was registetred a latent period of tremor start (sec), tremor intensity and rectal temperature. An intake of vegetative analizator caused minor tremor of the body which lasted 25 min. Also arekolin decreased a body temperature of animals in 2-3 degrees compared with standard norms. An intake of a drug compared with imipramin continued a duration of the latent period of tremor start and decreased a duration of a tremor, prevented temperature’s decrease compared with control pathology. Preventive intake of 2-oxoindolin derivative increased a latent period of a tremor in 2,5 times compared with control pathology. Also a substance decreased general tremor’s duration and prevented a temperature’s increase after cholinomimetics’ intake. Nicotine’s intake is caused by excitation of H-choloreactive structures, tremor’s development and hypothermia. E 38 substance decreased duration of the latent period and duration of tremor’s nicotine in 1,4 times compared with control.